Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.clinph.2013.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and familiarity enhance single-trial detectability of imagined movements with electroencephalography

Abstract: Follow this and additional works at: https://ir.lib.uwo.ca/anatomypub Part of the Anatomy Commons, and the Cell and Developmental Biology Commons Citation of this paper:Gibson, Raechelle M.; Chennu, Srivas; Owen, Adrian M.; and Cruse, Damian, "Complexity and familiarity enhance single-trial detectability of imagined movements with electroencephalography" (2014 AbstractObjective: We sought to determine whether the sensorimotor rhythms (SMR) elicited during motor imagery (MI) of complex and familiar actions cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 74 publications
(124 reference statements)
0
28
0
Order By: Relevance
“…The type of movement imagery can have a major effect on BCI performance, for example, [40] found that subjects who relied on visual imagination of hand movement performed worse than subjects who focused on the kinesthetic aspect of the same task. [41] found that subjects could attain better performance by imagining familiar actions.…”
Section: Introductionmentioning
confidence: 99%
“…The type of movement imagery can have a major effect on BCI performance, for example, [40] found that subjects who relied on visual imagination of hand movement performed worse than subjects who focused on the kinesthetic aspect of the same task. [41] found that subjects could attain better performance by imagining familiar actions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the sample of 14 patients recruited by Gibson et al (2014), some of them were ineligible for the fMRI and/or the EEG evaluation and only six could complete both procedures. Promising results have recently been found in EEG as well as in fMRI (Schnakers et al, 2009;Goldfine et al, 2011;Cruse et al, 2012b;Gibson et al, 2013;Holler et al, 2013;Naci and Owen, 2013). Better sensitivity may be observed with these protocols than with the one used in the present study, but since these protocols were performed by different teams in different groups of subjects it is difficult to determine precisely.…”
Section: Relative Place Of Eeg and Fmrimentioning
confidence: 64%
“…Indeed, in this protocol, the cross-validation design is a particularly delicate issue that has already been pointed out (Goldfine et al, 2013;Noirhomme et al, 2014) and that shows the strong influence of the temporal dependence between the test-set blocks on the classification accuracy. In recent studies avoiding this limitation, promising results have been found in healthy volunteers but also in some patients with DOCs (Gibson et al, 2013;Holler et al, 2013) but their replication on a larger scale is needed before clearly establishing whether they are sensitive enough to reliably capture awareness. By contrast, the conservatism of FDR correction is more a matter of debate.…”
Section: Command-following Taskmentioning
confidence: 92%
“…By using transcranial magnetic stimulation (TMS), higher motor-evoked potential (MEP) amplitude is found with more complex task, indicating an increased corticospinal excitability with increased task-complexity (Kuhtz-Buschbeck et al, 2003; Roosink and Zijdewind, 2010). Electroencephalography (EEG) studies show that sensorimotor rhythms (SMR) elicited during complex actions can be more reliably detected comparing with simple actions (Gibson et al, 2014). ECoG studies have found no evidence for increases in gamma power in subjects discriminating the strength of a somatosensory stimulus (Menon et al, 1996).…”
Section: Discussionmentioning
confidence: 99%